Boxing in Philadelphia: Tales of Struggle and Survival - Oppenheim, Gabe (Rowman & Littlefield Publishers, 2014)
Philadelphia was essentially the birthplace of boxing in America, the city where matches first took shape in the back of bars. Jack Johnson, the first black heavyweight champ, fought more times in Philly than any other city besides his hometown; Sugar Ray Robinson, perhaps the best boxer ever, fought under his first promotional contract in Philadelphia, appearing there twenty times; and Joe Louis, one of the greatest heavyweights of all time, was trained by a Philadelphia fighter. In Boxing in Philadelphia,Gabe Oppenheim examines the rise and fall of boxing in Philadelphia, and how it often mirrored the city’s own narrative arc. Originating from the tales told to Oppenheim by a retired Philadelphia trainer, this history of boxing is drawn from personal interviews with current and former fighters and managers, from attending the fights in local arenas, and from watching the boxers train in their gyms. In this book, Oppenheim opens a window into the lives of such fighters as Jimmy Young, Meldrick “The Kid” Taylor, Teon Kennedy, and Mike Jones, telling with remarkable detail their struggles, triumphs, and defeats. Throughout, Oppenheim weaves together cultural history, urban studies, and biographical sketches of past boxers to create this comprehensive account of Philadelphia and its fighters. Featuring an array of photographs and exclusive interviews, this book captures the unique history of Philadelphia boxing. It will interest boxing fans, those who enjoy sports and cultural histories, and of course, native Philadelphians who want to discover more about their city and their fighters.